PENTINGNYA INOVASI DALAM PENDIDIKAN: KAJIAN PUSTAKA TENTANG PERAN, IMPLIKASI, DAN TANTANGAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Abdul Wahab Syakhrani; Usman Usman (CV. Adiba Aisha Amira, 2025)
This study is a literature review that discusses the importance of innovation in education through an analysis of various literature and previous research results. This study highlights the role of innovation as a key factor in improving the effectiveness of the learning process, developing teaching methods, and achieving better educational outcomes. In addition, this study reviews the challenges faced in implementing educational innovation and how innovation can adapt to technological developments and social needs. With a synthesis of various scientific sources, this study provides in-depth insights into the contribution of innovation in strengthening the education system and shaping an adaptive and creative generation.